Evaluasi Kualitas Produk Dadih Dalam Bentuk Bubuk Yang Dikeringkan Dengan Sinar Matahari Dan Oven - L. Ibrahim (Jurnal Peternakan Indonesia (Indonesian Journal of Animal Science), 2006)
The research was conducted to compare the quality of curd in powder processed by using natural (sun) and oven drying. Results showed drying processes did not give significant effect on the quality of curd products. Curd powder produced by using natural drying had acidity of 1.50 %, pH 4.02, total number of bacteria of 2 x104 colony /gram, water content of 7.02 % and protein of 14.4 %, while that of dried by oven had acidity 1.46 %, pH 4.04, total bacteria 1.5 x10 ³ colony/ gram, water content 6.8 % and protein 14.02 %.